Comparison of the Efficacy of Topical Clobetasol Propionate 0.05% and Emolient versus Topical Clobetasol Propionate 0.05%, Emolient and Oral Vitamin D Supplement in the Treatment of Atopic Dermatitis - Noor ul Wara,; Shahid, Muhammad Waseem; Fatima, Kaneez; Irshad, Mushayada; Ali, Umar Abdul; Ghaus, Iqra (Indus Journal of Bioscience Research, 2025)
Objectives: Atopic dermatitis (AD) is a skin disorder affecting all age groups, but more common in toddlers and older children. This study aims to compare efficacy of topical treatment with oral vit D3 supplements plus standard topical treatment. Methods: An open-label comparative study was conducted at dermatology outpatient department of Pak Emirates Military Hospital, Rawalpindi from July 2024 till Dec 2024. Group A Received Topical Clobetasol Propionate 0.05% and Emolient while Group B received Topical Clobetasol Propionate 0.05%, Emolient and Vitamin D3 Supplement 800IU in form of oral drops. Mean SCORAD score before start of treatment and at the end of treatment was compared to measure efficacy of these treatment regimens. Percent decrease in mean score was calculated. Results: Vitamin D3 supplemetation yielded significant improvement in symptoms and severity of AD. Group A who received topical treatment only showed 60.2% reduction in mean SCORAD after 8 weeks of treatment while in Group B who received oral Vit D3 along with topical treatment, mean SCORAD was reduced by 72.2%. Difference in efficacy of these two treatment groups came out to be statistically significant. (p- value 0.037) Conclusion: Our study suggests that daily dose of oral vitamin D3 supplements might provide clinical improvement in children with AD. It should be considered as a relative adjuvant to the standard regimen of AD along with other oral and topical treatments.